Recombinant human growth hormone in the treatment of Turner syndrome - Bessie E Spiliotis (Therapeutics and Clinical Risk Management, 2008)
Bessie E SpiliotisDivision of Pediatric Endocrinology and Diabetes, Department of Pediatrics, University of Patras, School of Medicine, Patras, GreeceAbstract: Turner syndrome (TS) is a common chromosomal disorder in women that is associated with the absence of one of the X chromosomes. Severe short stature and a lack of pubertal development characterize TS girls, causing psychosocial problems and reduced bone mass. The growth impairment in TS seems to be due to multiple factors including an abnormal growth hormone (GH) – insulin-like growth factor (IGF) – IGF binding protein axis and haploinsufficiency of the short stature homeobox-containing gene. Growth hormone and sex steroid replacement therapy has enhanced growth, pubertal development, bone mass, and the quality of life of TS girls. Recombinant human GH (hGH) has improved the height potential of TS girls with varied results though, depending upon the dose of hGH and the age of induction of puberty. The best final adult height and peak bone mass achievement results seem to be achieved when hGH therapy is started early and puberty is induced at the normal age of puberty in a regimen mimicking physiologic puberty. The initiation of estradiol therapy at an age-appropriate time may also help the TS patients avoid osteoporosis during adulthood. Recombinant hGH therapy in TS seems to be safe. Studies so far show no adverse effects on cardiac function, glucose metabolism or any association with neoplasms but research is still in progress to provide conclusive data on long-term safety.Keywords: Turner syndrome, recombinant growth hormone, growth hormone deficiency, SHOX gene, hormonal replacement therapy